การออกแบบฟลูอิไดซ์เบดแบบหมุนเวียน: ผลของลักษณะแอลวาล์วในการไหลที่อุณหภูมิห้อง - พีรพล ฐิติอนันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
In this research, L-valve was used in the circulating fluidized bed to control solid circulation rate. The effect of L-valve configuration in cold-flow (the position of aeration tap, angle of L-valve, solid inventory and aeration flow rate) was studied by measuring the solid circulation rate. Coal which has the density of 1381 kg/m[superscript 3], particle size distribution between 500 and 5000 micron, average particle size of 740 micron and was categorized in group B and D in Geldart s classification was used. From this study, solid circulation rate at the position of 6 cm above the center of horizontal L-valve was higher than the position of 0 and 12 cm only when horizontal L-valve. The solid circulation rate was increased when aeration flow rate and angle of L-valve increased and it didn t depend on the solid inventory. Finally, the relationship between the solid circulation rate and these parameter was studied.